The genesis of Koper medieval statutes (1238–1423) - Darovec, Darko (Acta Histriae, 2023)
This paper presents an original analysis and reinterpretation of two documents from 1238 and 1239, which are the first to mention the Koper statutes but have thus far received only sporadic mentions in historiography. The paper is further predicated on the study of archival sources of the Venetian Senate from the Senato Misti collection for the period after the Koper rebellion against Venice in 1348 up until 1394 when the Doge of Venice reconfirmed the Koper statutes. It is established that at least from 1238 the commune of Koper acted according to its already complex statutes. These were, with some further redactions, in force until 1348, when, due to the rebellion of Koper, they were disregarded by the Venetian authorities until 1358, along with the dissolution of the city’s Major Council, and all of Koper’s city offices were restructured. After 1358, the sources testify that the Venetians restored the Koper City Council and offices to their pre-rebellion state, but not the statutes, although some statutory provisions were taken into account in individual administrative or judicial cases. The Koper statutes officially came into force again in 1394, and a slightly modified redaction appeared in 1423. However, in both cases without the right to exercise criminal justice and the defence of the city, which remained in the exclusive domain of the Venetian podesta and captain until the end of the Venetian Republic in 1797.
Keywords: Beneška republika; Istra; Koper; ne zaključna dela; severna Italija; srednjeveška zgodovina; srednji vek; statuti